PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA DI SMP PGRI 4 LABUHAN RATU - Apri Kurniasih; Dhoni Kurniawati; Septiani Selly Susanti; Siti Khomsiyati (LPPM STAI DARUSSALAM LAMPUNG, 2022)
ABSTRACT The government's policy in launching an independent curriculum is intended to improve the quality of education in Indonesia. During the education recovery period, namely 2022-2024, the independent curriculum is implemented in Sekolah Penggerak, SMK pusat Keunggulan, and Schools that are ready to implement the Independent Pathway Curriculum, while schools that are not ready to be given the independence to continue to use the 2013 curriculum or the emergency curriculum. The existence of assistance in implementing the independent curriculum at SMP PGRI 4 Labuhan Ratu is intended to provide understanding and training in preparing learning tools that will support the implementation of the independent curriculum in the future. Mentoring is carried out using the service learning method, where the companion team visits and provides training for three meetings with three materials, namely: open mind, an independent curriculum for junior high school level, and the use of an independent teaching platform. Evaluation at the mentoring implementation stage is that it is necessary to provide further assistance in the form of workshops on the preparation of textbooks, learning modules, and student project designs in all subjects in grade 7 SMP